2023
DOI: 10.3390/nu15183934
|View full text |Cite
|
Sign up to set email alerts
|

Causal Link between Gut Microbiota, Neurophysiological States, and Bone Diseases: A Comprehensive Mendelian Randomization Study

Shaoting Luo,
Zhiyang Chen,
Linfang Deng
et al.

Abstract: Increasing evidence highlights a robust correlation between the gut microbiota and bone diseases; however, the existence of a causal relationship between them remains unclear. In this study, we thoroughly examined the correlation between gut microbiota and skeletal diseases using genome-wide association studies. Linkage disequilibrium score regression and Mendelian randomization were used to probe genetic causality. Furthermore, the potential mediating role of neuropsychological states (i.e., cognition, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…By focusing on the gut microbiota, we identified a microbial community that affects both: order Burkholderiales.id.2874. In previous studies, a causal relationship between Burkholderiales and lumbar spine fractures has been identified, corroborating our findings that this genus indeed has an unknown connection with bone (25). Building on prior research, we expanded the related mechanisms by incorporating the impact on osteoclasts and predicting their potential downstream targets.…”
Section: Discussionsupporting
confidence: 82%
“…By focusing on the gut microbiota, we identified a microbial community that affects both: order Burkholderiales.id.2874. In previous studies, a causal relationship between Burkholderiales and lumbar spine fractures has been identified, corroborating our findings that this genus indeed has an unknown connection with bone (25). Building on prior research, we expanded the related mechanisms by incorporating the impact on osteoclasts and predicting their potential downstream targets.…”
Section: Discussionsupporting
confidence: 82%
“…N, ALP, claudin-1, and occludin. This suggests that Burkholderiales can repair damage to the gut barrier, promote bone formation, and increase bone density, and that Burkholderiales itself has a unique ability to degrade a variety of compounds (including exogenous substances), and its effect on bone may play an indirect osteoprotective role by eliminating potential pathogenic cytokines in the gut, enriching the diversity of the intestinal microbiota in conjunction with other bacterial flora ( Wicaksono et al, 2023 ), and maintaining the integrity of the intestinal tract ( Luo et al, 2023 ). Meanwhile, this study also identified g_Akkermansia, g_Parabacteroides, g_Alistipes, g_Parasutterella, and g_Muribaculum as possible differential genera affecting BMD, among which B. Akkermansia is a potential probiotic located in the mucus layer of the intestine, which produces a variety of mucin-degrading bio-enzymes and ferments to produce SCFAs ( Collado et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%